Determine The Best Coordinate Transformation Method Between The WGS84 And Local Coordinate Systems For Facility Deformation Monitoring - احمد محسن; محفوض ندى (Latakia University Journal -Engineering Sciences Series, 2021)
The transformation of two-dimensional and three-dimensional coordinates is one of the traditional procedures in survey work, but when the global navigation satellite systems (GNSS) are used in determining the location, then transformation the three-dimensional coordinates becomes a necessary application. The main objective of this research is to determine the best method for transformation 3D coordinates measured by GNSS to 3D local coordinate system in order to observe a facility deformation. The results using the " Trans LT" program showed that the best method to transform the coordinates is the " 8 Affine", and the worst are the "Bursa’ and " Molodensky – badekas " conformal transformation methods, after taking into account the number and distribution of the common points with an emphasis on the need to correct the geoidal undulation of the measured levels in GNSS.